PLACE OF FOREIGN EXCHANGE REGULATION IN FOREIGN EXCHANGE RELATIONS’ MANAGEMENT - Шелудько, Сергій (Socio-economic relations in the digital society, 2019)
It is studied the essence and structure of the process of foreign exchange relations’ management. It is established that foreign exchange policy, foreign exchange regulation and foreign exchange control are elements of thisprocess. It is defi ned the relationship between these concepts, which manifests itself in the generality of their subjectmatter. For substantiation a place of the foreign exchange regulation in the foreign exchange relations’ management, itis developed and studied its system. It is proved that the task of foreign exchange regulation is the ordering of foreign exchange relations, which determines its key place in the process of their management.
Keywords: foreign exchange control; foreign exchange policy; foreign exchange regulation; foreign exchange relations; management